Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium